Stable cyclopropene-containing analogs of the amino acid neurotransmitter glutamate. Issue 22 (30th May 2019) - Kumar, Pratik; Huang, Wei; Shukhman, David; Camarda, Frank M.; Laughlin, Scott T.
Graphical abstract: Highlights: Applying bioorthogonal chemistry to neuroscience with cyclopropene bearing neurotransmitter analogs. Shorter and half-gram scale synthesis of cyclopropene-analogs of glutamate. Generation of novel forms of structurally constrained glutamate analogs. Abstract: As a neurotransmitter, the amino acid glutamate has been the subject of efforts to generate structural analogs with unique properties. Here we report a practical, half-gram synthesis of two cyclopropene-containing glutamate analogs. These analogs are stable in solution, in the presence of the biological nucleophile glutathione, upon concentration, and during long-term storage, while maintaining their amenability to photo- or enzyme-caging and reactivity with bioorthogonal reaction partners like s-tetrazine or light-activated tetrazoles.